The Out of Africa Hypothesis of Comparative Economic Development: Common Misconceptions - Quamrul H. Ashraf; Oded Galor; Marc P. B. Klemp (Center for Economic Studies and ifo Institute (CESifo), 2019)
The importance of the prehistoric migration of anatomically modern humans from Africa for comparative economic development has been the focus of a vibrant research agenda in the past decade. This influential literature has attracted the attention of some scholars from other disciplines, and in light of existing methodological gaps across fields, has perhaps unsurprisingly generated some significant misconceptions. This article examines the critical views expressed by some scholars from other disciplines, and establishes that they are based on fundamental misunderstandings of the statistical methodology, the conceptual framework, and the scope of the analysis that characterize this influential literature.
Keywords: O11; N10; N30; Z10; 330; comparative development; interpersonal population diversity; the out of Africa hypothesis